Reflection and transmission of regular waves from/through single and double perforated thin walls - Chioukh, Nadji; Cevik, Esin; Yuksel, Yalcin (CHINA OCEAN PRESS, 2017)
In this paper, reflection and transmission coefficients of regular waves from/through perforated thin walls are investigated. Small scale laboratory tests have been performed in a wave flume firstly with single perforated thin Plexiglas plates of various porosities. The plate is placed perpendicular to the flume with the height from the flume bottom to the position above water surface. With this thin wall in the flume wave overtopping is prohibited and incident waves are able to transmit. The porosities of the walls are achieved by perforating the plates with circular holes. Model settings with double perforated walls parallel to each other forming so called chamber system, have been also examined. Several parameters have been used for correlating the laboratory tests' results. Experimental data are also compared with results from the numerical model by applying the multi-domain boundary element method (MDBEM) with linear wave theory. Wave energy dissipation due to the perforations of the thin wall has been represented by a simple yet effective porosity parameter in the model. The numerical model with the MDBEM has been further validated against the previously published data.
Keywords: wave-structure interaction; perforated thin walls; boundary element; experimental tests; wave reflection; wave transmission; VERTICAL BARRIERS; BREAKWATER; DIFFRACTION; PLATE; Engineering; Water Resources